K0MPARASI EKSTENSI JURU SITA DALAM HUKUM ACARA PERADILAN TATA USAHA NEGARA TERHADAP HUKUM ACARA PERDATA - Benny Oktariani, Putu; A. Martana, Nyoman; Sudjana, I Ketut (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 04, Mei 2013, 2013)
A bailiff process server is a court authority in charge of confiscating assets.According to the law, bailiff/ process server constitutes an official of the court whoassists the clerk of the court by the instruction from the head of the court with theresponsibility and duty of asset confiscation or execution.
Keywords: Court Official, Assist of Clerk, Confiscation